A Case Report on Internal Bleacing of a Discolored Central Incisor Using 35% Hydrogen Peroxide - Aryo Sutowijoyo; Prima Nerito (Biofaal Journal, 2025)
A patient presented with tooth discoloration due to trauma, which had caused a tooth to become non-vital. Such trauma can damage the pulp tissue, eventually leading to necrosis and discoloration over time. In cases like this, internal bleaching is a treatment procedure aimed at improving the color of non-vital teeth. Discoloration of teeth after endodontic treatment often raises concerns for both patients and dentists. Whitening the tooth after root canal treatment is important to restore its original color before a permanent restoration is placed. The objective of this report is to present the successfull outcome of internal bleaching in patient who had undergone root canal treatment en years earlier. A 39-year-old male presented with a complaint of discoloration in the right maxillary central incisor. The patient had a history of root canal treatment on the tooth performed ten years prior. Radiographic examination confirmed that tooth 11 had undergone root canal treatment. Internal bleaching was performed on tooth 11, which appeared darker than the adjacent teeth. Whitening was carried out using 35% hydrogen peroxide. By the fourth visit (one week after the third application), the tooth color had changed to shade D3, which matched the desired color. This indicated a significant improvement in shade. Internal bleaching using 35% hydrogen peroxide resulted in color enhancement consistent with patients expectations. The treatment proved effective in restoring the esthetics of a non-vital tooth discolored due to trauma.